2000
DOI: 10.1080/00140130050174482
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole-body restriction on task performance

Abstract: Many occupations, particularly involving maintenance operations, require individuals to perform both physical tasks and mental tasks in restricted spaces. Researchers have examined physical task performance under various restrictions; however, little research has investigated the effects of restricted space on cognitive tasks. Cognitive task performance in restricted spaces presents cognitive demands (i.e. the task itself) as well as additional physical demands (e.g. awkward postures), which may adversely affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…One such group of individuals that have been the target of such research is mechanics and maintenance people. For example, many aircraft maintenance tasks require the maintenance staff to perform inspection and diagnostic activities within the narrow confines of aircraft structures, [9] like airplane mechanics and others, scale technicians are also forced to work in a confined or restricted space.…”
Section: Moving Around In the Pitmentioning
confidence: 99%
See 3 more Smart Citations
“…One such group of individuals that have been the target of such research is mechanics and maintenance people. For example, many aircraft maintenance tasks require the maintenance staff to perform inspection and diagnostic activities within the narrow confines of aircraft structures, [9] like airplane mechanics and others, scale technicians are also forced to work in a confined or restricted space.…”
Section: Moving Around In the Pitmentioning
confidence: 99%
“…Mozrall et al [9] examined the effects of restricted body position on task performance. In their study, the subjects were asked to perform an inspection task in an experimentally constructed restricted space.…”
Section: Moving Around In the Pitmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that we take these dual sets of measurements on a system involving a subsystem as complex as a human operator, should we be surprised if the measurements dissociate (Yeh and Wickens 1988)? To give one recent example, Mozrall et al (2000) looked at the e V ects of quite severely restricted physical workspaces. They found that participants gave consistent and easily interpretable measures of the costs of performance (e.g.…”
mentioning
confidence: 99%